Submission on the progress and outcomes of the first phase of implementing the Article 6.8 work programme activities, and views on improving and recommending the schedule for implementing the work programme activities for the second phase - Alliance of Bioversity and CIAT; CGIAR (2024)
This submission is made in response to the invitation to observers to submit views and information on the progress and outcomes of the first phase of implementing the Article 6.8 work programme activities (See Annex 1), and views on improving and recommending the schedule for implementing the work programme activities for the second phase1 . We understand that this request for submissions is to inform the “expedited and simple assessment2 ” of the progress and outcomes of the first phase of implementing the work programme activities at the 6th meeting of the Glasgow Committee on Non-Market Approaches (GCNMA), as agreed at COP 26. And that the “expedited and simple assessment” would take place in November 2024 (at COP29). The second phase of Article 6.8 implementation will take place during 2025–2026, focusing on fully implementing the work programme activities following a learning-by-doing approach and drawing on inputs from the first phase. During the first phase, it was agreed that UNFCCC National Focal Points (NFPs) will have responsibility for Article 6.8 activities, with several roles for NFPs now identified throughout decisions made since 2021. These roles and responsibilities include being able to identify Non-Market Approaches (NMAs), engagement with the Article 6.8 web platform, coordination with NFPs in other countries, ensuring participation of stakeholders, as well as other important roles, such as to ensure NMAs respect human rights, avoid negative impacts and promote synergies between mitigation and adaptation, and contribute to implementation of Nationally Determined Contributions (NDCs). Hence, the expertise and capacity of NFPs is an extremely important consideration, requiring readiness support to enable the improved implementation of the work program during the second phase.